The impact of Semaglutide on weight loss and inflammation in people with HIV. An observational prospective study in Greek population. - Petrakis, Vasileios; Rafailidis, Petros; Panopoulou, Maria; Konstantinidis, Theocharis; Tsantes, Andreas G.; Babaka, Nikoleta; Papazoglou, Dimitrios; Panagopoulos, Periklis (Experimental and Clinical Endocrinology & Diabetes)
Introduction: The existing literature on the effects of semaglutide in people with HIV (PWH) and diabetes mellitus remains limited. The aim of the present study is to evaluate the effect of semaglutide on weight control and inflammation in PWH. Patients and Methods: This is a prospective observational study that included PWH with type 2 diabetes mellitus monitored at the HIV Unit of the University General Hospital of Alexandroupolis and a matched control group of non-HIV individuals. Demographic, anthropometric, and clinical characteristics, including HIV-related data and comorbidities were reported. All participants received semaglutide with a gradual dose increase to 1 mg once weekly. Body Mass Index (BMI), glycosylated hemoglobin (HbA1c), and inflammatory markers (IL-6, TNF, hsCRP, sCD14, CD4/CD8 ratio) were recorded at baseline and at 6, 12, 18, and 24 months. Results: A total of 50 participants (PWH: n=25; non-HIV: n=25) were included. At baseline, the mean BMI was 35.2±8.0kg/m2 for PWH and 36.1±6.0kg/m2 for non-HIV controls. Semaglutide treatment resulted in significant and sustained weight loss in both groups (p<0.001). At 24 months, the median weight loss was -14.6 kg in the PWH group and -18.8 kg in the non-HIV group for those with a baseline BMI >35kg/m2. Glycemic control also improved significantly, with mean HbA1c decreasing from 7.7%±1.23 to 5.2%±1.02 in PWH (p<0.001), and from 7.9%±1.16 to 5.6%±1.21 in non-HIV controls (p<0.001). Significant reductions were observed in hsCRP and sCD14 levels in both cohorts. A unique finding was the significant increase in the CD4/CD8 ratio in the PWH group, from a mean baseline of 0.54±0.12 to 0.83±0.14 at 24 months (p<0.001), a change not seen in the non-HIV controls. Conclusion: Semaglutide appears to be an effective and safe option for weight reduction and inflammation control in PWHIV. Further studies with a larger number of patients are necessary to substantiate these findings.